2010
DOI: 10.2353/ajpath.2010.091131
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Proliferation During Liver Regeneration Is Impaired in Mice with Methionine Diet-Induced Hyperhomocysteinemia

Abstract: Elevated homocysteine levels are defined as hyperhomocysteinemia (HHcy), a disorder that is associated with cardiovascular and neurodegenerative diseases as well as with hepatic fibrosis. Recent studies have shown that HHcy promotes hepatic injury by increasing oxidative stress. Although homocysteine induces cell cycle arrest in a variety of different cell types, it is not known whether HHcy has a definitive role in hepatocyte proliferation during liver regeneration. In this report, we investigated the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…A recent study has confirmed that TRB3 is a novel target gene of CHOP involved in the coordination of apoptosis during ER stress [28]. Our recent study indicates that expression of TRB3 is elevated in livers of mice with hyperhomocysteinemia [22]. In the current study, homocysteine induces TRB3 expression through the ER stress pathway in cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…A recent study has confirmed that TRB3 is a novel target gene of CHOP involved in the coordination of apoptosis during ER stress [28]. Our recent study indicates that expression of TRB3 is elevated in livers of mice with hyperhomocysteinemia [22]. In the current study, homocysteine induces TRB3 expression through the ER stress pathway in cultured hepatocytes.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies indicate that TRB3 inhibits the transmission of the Akt signal [22], [30]. Since phosphorylation of Akt at Ser473 was tightly correlated with its activation, we examined the effect of homocysteine on phosphorylation of Akt (Ser473).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wei-Hua et al showed that impaired liver regeneration in mice with hyperhomocysteinemia (HHcy) was also correlated with reduced cyclins and elevated expression of p53 and p21 Cip1 [16]. In contrast, p21 Cip1 knockout mice display accelerated hepatocyte proliferation after PH through G 1 phase.…”
Section: Introductionmentioning
confidence: 99%